2020
DOI: 10.3389/fpls.2019.01736
|View full text |Cite
|
Sign up to set email alerts
|

Phytoliths in Inflorescence Bracts: Preliminary Results of an Investigation on Common Panicoideae Plants in China

Abstract: Phytoliths in the inflorescence of Poaceae plants can be of high taxonomic value in some archaeological contexts and provide insight into plant taxonomy and crop domestication processes. In this study, phytoliths in every inflorescence bract of 38 common Panicoideae weeds and minor crops in China were studied. Based on dissection of the inflorescence into different bracts using a treatment that retained the phytoliths anatomical position, observations of inflorescence phytoliths types and distribution were des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 76 publications
(133 reference statements)
2
33
0
Order By: Relevance
“…However, we found that phytolith types and production in species belonging to different genera of the same family can be very different. Such results suggest the possibility of identification of taxa on the genus level using phytolith analysis, which is in consist with the study of grasses 22 , however, studies that involve more species and more samples of species are needed to confirm such findings. To date, no especially diagnostic types of phytoliths have been identified for broad-leaved trees in general or a certain family.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, we found that phytolith types and production in species belonging to different genera of the same family can be very different. Such results suggest the possibility of identification of taxa on the genus level using phytolith analysis, which is in consist with the study of grasses 22 , however, studies that involve more species and more samples of species are needed to confirm such findings. To date, no especially diagnostic types of phytoliths have been identified for broad-leaved trees in general or a certain family.…”
Section: Discussionmentioning
confidence: 87%
“…1-15) which we found in the fruit husk of Aleurites moluccana (which could be used as food or sauce in Malaysia and Indonesia), is also noteworthy as it has not been reported yet. Such silicification in fruit husks might be a protection strategy 22,66 , and the presence of this type may provide insight into ancient plant resource exploitation. In this study, we have provided an illustration of several distinct phytolith types we observed in the common broad-leaved trees in temperate China, and reported that there appears to be little difference in broad-leaved trees phytolith production between the northern and the southern regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 , 4 and Supplementary Tables S3 – 4 ). During phytolith morphological analysis of the sediments from Trench Y82 54 (see Supplementary Text), we encountered phytoliths in anatomical connection, or multicellular structures (also known as silica skeletons 66 or articulated groups 67 ), composed of interdigitating phytolith morphotypes 68 , 69 similar to Panicum miliaceum in ten samples (Table S1 ). In general, phytolith preservation was good across all samples (Supplementary Text) as is typical for archaeological sites (or tells) in Southwest Asia where phytoliths are removed from the silica cycle 70 73 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, five of the nine genera representing millets and their wild relatives 81 are present in modern Iraq ( Digitaria , Echinochloa, Panicum , Paspalum , Setaria , and Sorghum ) (Supplementary Table S6 ) 17 , 80 . Thus, it is necessary to use at least five diagnostic criteria to ensure secure species-level identifications of millet inflorescence phytoliths (Supplementary Table S5 ) 68 , 75 77 , 82 . Like phytoliths from grass inflorescences, bilobate short cells can be used to distinguish between domesticated millet species 83 .…”
Section: Introductionmentioning
confidence: 99%